EFL Higher Students’ Experiences in Apps-based Learning for Virtual Presentation - Ma'ruf, Zidni; Muhamad Nazarudin Asyidiq; Fujiya, Nenden Sri (The Indonesian Institute of Science and Technology Research, 2024)
As the Indonesian government and most countries forbade traditional face-to-face teaching and learning in the world during the COVID-19 pandemic, virtual teaching and learning through some apps have increased significantly, and one among them is Zoom. This qualitative research with a case study approach aims to explore EFL higher students’ experiences in App-based learning specifically for virtual presentation. Six students participated in this research, and the researchers got through purposive sampling. The open-ended interview was the primary data collection used in this research to give a clear picture and deep understanding of EFL higher students' experience through App-based learning for virtual presentation. All the interview data were recorded, transcribed, analyzed, and divided into some themes. Further, member checking was done by the researchers to develop the high trustworthiness of the research. This research revealed at least two themes: advantages (free from space-time and increasing speaking ability) and disadvantages (costly and lousy connection). Further, suggestions and recommendations were offered to all related parties.